Analisis Financial Crunch Pada Industri Perbankan Syariah Saat Krisis Keuangan Global 2008 - Muhammad Sobar Johari (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2014)
Global financial crisis that happened in 2008 has affected banking world in Indonesia. This causes bank conducting more selective credit policy so that it can emerge credit crunch phenomenon. Credit crunch also possibly happens in sharia banking that are often called as financial crunch. This can be proven with a rapid third party capital growth but do not be accompanied by a significant credit growth. This study aims to analyze whether financial crunch has happened in sharia banking in Indonesia when global financial crisis in 2008 and to examine affecting factors of credit in sharia banking industry in Indonesia. The study generally shows that financial crunch do not happen in Indonesian sharia banking. It means that credit delivery of sharia banking is consistent between prior and after global financial crisis in 2008. Several factors that affect on credit delivery in sharia banking are third party capital collection, CAR, NPF, GDP and SWBI/SBIS. Third party capital, capital adequacy ratio (CAR) have a positive significant effect on sharia banking credit delivery, whereas non performing finance (NPF), gross domestic product and SWBI/SBIS have a negative effect on sharia banking credit. Keywords: credit crunch, financial crunch, third party capital, CAR, NPF, GDP and SWBI/SBIS.